Evolution of the haemagglutinin-esterase gene of influenza C virus - Muraki, Yasushi; Hongo, Seiji; Sugawara, Kanetsu; Kitame, Fumio; Nakamura, Kiyoto (Journal of General Virology, 1996)
The nucleotide sequences of the haemagglutininesterase (HE) genes of 18 influenza C virus strains isolated in Japan during the period from 1964 to 1988 (11 published and 7 new sequences) were analysed to examine their evolutionary relationships. The phylogenetic tree constructed by the maximum parsimony method revealed the existence of four discrete lineages (I to IV), one of which (lineage III) may have died out in the late 1970s. Sequential evolution was demonstrated within seven strains of lineage I, which allowed estimation of an evolutionary rate of 0.49 × 10−3 nucleotide substitutions per site per year, a value corresponding to about one-ninth of the rates of human influenza A virus haemagglutinin genes. In the previously proposed immunodominant region on HE protein (positions 178 to 217), there was little or no amino acid sequence divergence among viruses on the same lineage although considerable divergence was seen among those on different lineages, raising the possibility that immune selection may not have played a significant role in the evolution of the glycoprotein, at least not after separation into lineages occurred. It was also found that the HE genes of the seven isolates obtained outside Japan during 1966–1983 could be each assigned to one of lineages I, II and IV, which suggests that influenza C virus is capable of spreading worldwide.